2016
DOI: 10.1111/nph.13870
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms whereby the green alga Chlorella ohadii, isolated from desert soil crust, exhibits unparalleled photodamage resistance

Abstract: SummaryExcess illumination damages the photosynthetic apparatus with severe implications with regard to plant productivity. Unlike model organisms, the growth of Chlorella ohadii, isolated from desert soil crust, remains unchanged and photosynthetic O 2 evolution increases, even when exposed to irradiation twice that of maximal sunlight.Spectroscopic, biochemical and molecular approaches were applied to uncover the mechanisms involved.D1 protein in photosystem II (PSII) is barely degraded, even when exposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(109 citation statements)
references
References 98 publications
(160 reference statements)
3
102
4
Order By: Relevance
“…Further indirect evidence on the participation of 1 O 2 in photoinhibition of PSII also varies, as the modification of the recombination reactions of PSII toward non-1 O 2 -producing direction provides protection against photoinhibition [326], whereas the protection offered by NPQ is very limited [327], suggesting that the photoinhibition of PSII may not depend only on the excitation of Chl [320,328]. The photoinhibition-tolerant green alga Chlorella ohadii exhibits a recombination reaction model that is expected to lead to low 1 O 2 production [329].…”
Section: Damage To Psiimentioning
confidence: 99%
“…Further indirect evidence on the participation of 1 O 2 in photoinhibition of PSII also varies, as the modification of the recombination reactions of PSII toward non-1 O 2 -producing direction provides protection against photoinhibition [326], whereas the protection offered by NPQ is very limited [327], suggesting that the photoinhibition of PSII may not depend only on the excitation of Chl [320,328]. The photoinhibition-tolerant green alga Chlorella ohadii exhibits a recombination reaction model that is expected to lead to low 1 O 2 production [329].…”
Section: Damage To Psiimentioning
confidence: 99%
“…Alternatively to genetic engineering and mutation/phenotypic selection, an alternative approach consists into sampling and evaluating algal biodiversity, particularly in extreme environments which might provide interesting performance when such strains are grown in optimal conditions. An example of this is the case of Chlorella ohadii, a chlorella strain from the Sinai desert, which was reported to exhibit high productivity and the robustness of growth [94,95].…”
Section: Bioengineering Response To Light Fluctuations and Improving mentioning
confidence: 99%
“…have been proved to be a good option for biodiesel production Mata et al, 2010;O'Grady and Morgan, 2011). Furthermore, a very recently discovered species of Chlorella, Chlorella ohadii (Treves et al, 2016), has been shown to have a growth potential and a tolerance to high irradiance extraordinary for eukaryotes, which may immensely increase the biomass productivity of an algal production plant. Unfortunately, this strain is not easily available at the moment and research on its application potential is therefore somewhat problematic.…”
mentioning
confidence: 99%